2016
DOI: 10.1177/2167696816653856
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Ethnic Differences in Young Adults’ Emotional Reactions to Parental Punitive and Minimizing Emotion Socialization Practices

Abstract: Gender and ethnic differences in young adults' emotional reactions to parental punitive and minimizing emotion socialization practices. Emerging Adulthood, 5, 83-92.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 44 publications
(59 reference statements)
1
20
0
Order By: Relevance
“…In addition, it has been observed that parent-child communication problems do not affect smartphone dependency in adolescent boys but affected smartphone dependency in adolescent girls [60]. Adolescent girls are likely to be more sensitive or attuned to parents' negative responses [36] and thus they are more influenced by negative parental practices, which may increase the likelihood of smartphone dependency. Our findings regarding the moderating role of gender indicate the need for gender-specific intervention strategies to decrease smartphone addiction among adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been observed that parent-child communication problems do not affect smartphone dependency in adolescent boys but affected smartphone dependency in adolescent girls [60]. Adolescent girls are likely to be more sensitive or attuned to parents' negative responses [36] and thus they are more influenced by negative parental practices, which may increase the likelihood of smartphone dependency. Our findings regarding the moderating role of gender indicate the need for gender-specific intervention strategies to decrease smartphone addiction among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of adolescent girls can make them more sensitive to parents' parenting styles. In particular, women tend to focus more on the negative aspects [33,34], making them more vulnerable to negative relationships, namely, negative parenting [35,36]. In addition, being an adolescent girl may moderate the effects of negative parenting style on adolescent smartphone dependency more than being an adolescent boy.…”
Section: The Moderating Role Of Child Gendermentioning
confidence: 99%
“…Although previous research has shown that negative parental behaviours tend to affect to boys and girls in a different way, to the best of our knowledge, it is the first study that reports these results applied to cyberbullying. In this sense, recent studies have reported that negative parenting (especially those parental practices related to the management of misbehaviour such as high control or punishment) increases the likelihood of girls to develop externalizing and aggressive behaviours [55,56] and that girls seem to be more affected by negative parental practices which favour that they feel more hurt and less loved than boys [57]. This evidence helps to understand our findings which suggest that negative parenting in girls is associated not only to the lack of skills to cope cyber-victimization situations, but also to an important maladjustment which also leads them to bully others through ICT.…”
Section: Discussionmentioning
confidence: 99%
“…Two candidates to consider as links between parent ES and youth outcomes are guilt‐proneness and shame‐proneness, given that they have been associated in prior research with a number of parenting behaviors (e.g., Parisette‐Sparks et al, ), including ES (e.g., Perry et al, ), as well as with youth outcomes such as depression and compassion for others (Tangney & Dearing, ). Although shame and guilt have historically been used interchangeably, several important distinctions differentiate them (see Tangney & Dearing, , for a review).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Like discrete emotion expressed, gender of parent and child also appears to influence the way emotions are socialized (e.g., Le, Berenbaum, & Raghavan, 2002;Perry, Leerkes, Dunbar, & Cavanaugh, 2016). Although ES research has predominantly focused on mothers' parenting behaviors (e.g., Sanders et al, 2015), preliminary work indicates that fathers play a unique role in ES (e.g., Nelson, O'Brien, Blankson, Calkins, & Keane, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%